Pathological mechanisms of connexin26-related hearing loss: Potassium recycling, ATP-calcium signaling, or energy supply? - Chen, Penghui; Wu, Wenjin; Zhang, Jifang; Chen, Junmin; Li, Yue; Sun, Lianhua; Hou, Shule; Yang, Jun (Frontiers in Molecular Neuroscience, 2022)
Hereditary deafness is one of the birth defects with the highest incidence. GJB2 gene mutation accounts for about 50% of the genetic etiology. Gap junction protein (connexin, Cx) 26 encoded by GJB2 gene, which is responsible for intercellular substance transfer and signal communication, plays a critical role for hearing acquisition and maintenance. Auditory character of mice models with Cx26 different genetic manipulation can be classify into profound congenital deafness and late-onset progressive hearing loss, which mimic the various phenotype of patient with GJB2 mutations. Recent experiments demonstrated the physiopathological changes including endocochlear potential reduction, active cochlear amplification impairment, cochlear developmental disorders, etc. of connexin26 deficiency mice are difficult to explain by one simple pathological mechanism. Here, this review summarizes three main hypotheses to explain pathological mechanisms of connexin26-related hearing loss: potassium recycling disruption, ATP-calcium signaling propagation disruption, and energy supply dysfunction. Elucidating pathological mechanism underlying connexin26-related hearing loss can help develop new protective and therapeutic strategies for this common deafness. It is worthy of further study on the detailed cellular and molecular upstream mechanisms to modify connexin (channel) function.